1989
DOI: 10.1007/bf01025605
|View full text |Cite
|
Sign up to set email alerts
|

Conformational change of bovine serum albumin by heat treatment

Abstract: The thermal denaturation of bovine serum albumin (BSA) was studied at pH 2.8 and 7.0 in the range of 2-65 degrees C. The relative proportions of alpha-helix, beta-structure, and disordered structure in the protein conformation were determined as a function of temperature, by the curve-fitting method of circular dichroism spectra. With the rise of temperature at pH 7.0, the proportion of alpha-helix decreased above 30 degrees C and those of beta-structure and disordered structure increased in the same temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
107
1
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(127 citation statements)
references
References 20 publications
14
107
1
5
Order By: Relevance
“…However, Takeda et al reported a conformational change by heat treatment of BSA namely, the α-helical structure began to decrease and convert into a β-structure at over 40°C. 30,31) This result was a little different from our observation that there was no remarkable conformational change up to 60°C. We used Fraction V of BSA, whereas Takeda et al utilized high-pure crystallized BSA, so it seems to show different stability at high temperature.…”
Section: Discussioncontrasting
confidence: 56%
“…However, Takeda et al reported a conformational change by heat treatment of BSA namely, the α-helical structure began to decrease and convert into a β-structure at over 40°C. 30,31) This result was a little different from our observation that there was no remarkable conformational change up to 60°C. We used Fraction V of BSA, whereas Takeda et al utilized high-pure crystallized BSA, so it seems to show different stability at high temperature.…”
Section: Discussioncontrasting
confidence: 56%
“…Unfortunately, DFOPS imaging at this magnification is limited insofar as the translucent material cannot be conclusively characterized and no irrefutable distinction can be made between the various translucent constituents. Despite these limitations, it is arguable that the blood-borne translucent bodies are comprised of thermally denatured and precipitated plasma proteins, which have a lower irreversible denaturation threshold than lipoproteins or cell membranes [20,26] due to the lack of thermodynamically stabilizing phospholipids [27]. Generated intraluminal isotherms may therefore be subcritical for thermolysis and agglutination (>80˚C) [24] of red blood cells, yet exceed the threshold values for irreversible plasma protein denaturation (i.e., >45˚C for serum albumin) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on external factors, the tested component of the biosensor matrix can be crushed in whole or in part only. Takeda et al [14] have discovered that secondary structural changes occur only after the reduction of disulfide bones. Then the helix content drops from 66% to 25%, the β structure content increases from 3% to 19%.…”
Section: Resultsmentioning
confidence: 99%
“…BSA conformational changes caused by varying pH or temperature were the subject of earlier research [14,15]. Reports on the effect of non-ionizing electromagnetic radiation at 200 MHz frequency applied in fractional doses to protein were not found.…”
Section: Introductionmentioning
confidence: 99%